Estudio de prefactibilidad para la instalación de una planta productora de crema de guacamole (Persea americana millar) con chía (Salvia hispanica) - Mansilla De Ita, Jorge Andrés (2020)
In Peru we have several avocado producing areas, which are: La Libertad, Lima, Ica and Junín. The departments above concentrate around 80% of the production from Peru, being Hass the most demanded avocado varieties both nationally and internationally. The results of growing trend over the demand, the new trends of healthy eating and taking Mexico as reference, country which trades the processed avocado in different presentations offering an industrialized fruit; originates the necessity of developing new alternatives that allow offering the consumers products made from avocado, such as guacamole with chia. This is an innovative idea for giving added value to the avocado through its production as puree. This mixture was chosen because of the fruit properties such as the seed, among the most important are: high fiber content, fatty acids and omega 3 which contributes to the body on enhancing the appearance of the skin, help prevent neurological diseases, regulate cholesterol levels, among others. The research work herein seeks to determine the technical, economic and market viability of the production plant of guacamole cream with chia. By analyzing the demand, we determined that our target market is the population of Metropolitan Lima of SES (Socioeconomic Status) A and B who have a healthy lifestyle.